Koinfeksi Sifilis Sekunder, Condyloma Acuminata dan Human Immundeficiency Virus (HIV) pada Pria Homoseksual - Ahmad Fiqri; Endra Yustin ES (PT Dexa Medica, 2022)
Introduction: Men who have sex with men (MSM) have higher risk of contracting sexually transmitted infections (STIs) such as syphilis, one of chronic and systemic STI. HIV and HPV infection can be risk factors for syphilis infection, while coinfection between syphilis and HIV facilitates the course of the two diseases. Case: A 22-year-old homosexual man complained of red scaly patches on both palms and feet, no itching, hair loss and lumps in the genital area. Examination revealed nonscarring alopecia on occipital region, bilateral patches with multiple erythematous plaques partly confluent hyperpigmentation and an overlying scale on palmar and plantar region, also multiple nodule papules with pale red smooth surface on perineal region. The acetowhite examination at the verrucous lesion was positive. The results of the CD4 examination was 112 cells/µl, VDRL/RPR was reactive 1:256; and TPHA was also reactive >1:5,120. Histopathological examination of the skin showed the features of skin syphilis and condyloma acuminata. Immunohistochemistry test revealed brownish Spirochaeta. The patient was diagnosed with secondary syphilis coinfection, condyloma acuminata, and HIV. Conclusion: We found a case of MSM patient that was coinfected with secondary syphilis, condyloma acuminata, and HIV. HPV and HIV infection are often coexisting because they both increase the risk of sexually transmitted infections.